2003
DOI: 10.1080/713610925
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Functions of Lipids and Fatty Acids in Teleost Fish

Abstract: Lipids and their constituent fatty acids are, along with proteins, the major organic constituents of fish, and they play major roles as sources of metabolic energy for growth including reproduction, and movement including migration. Furthermore, the fatty acids of fish lipids are rich in ω3 long chain, highly unsaturated fatty acids (n-3 HUFA) that have particularly important roles in animal nutrition, including fish and human nutrition, reflecting their roles in critical physiological processes. Indeed, fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

77
1,718
11
56

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 2,102 publications
(1,961 citation statements)
references
References 277 publications
77
1,718
11
56
Order By: Relevance
“…The clear preference of production of PGE 2 over PGE 3 , and a general preference of n-6 eicosanoids over their n-3 counterparts (eg PGF 2α and PGF 3α , and also the stable nonenzymatic hydrolytic products of PGI 2 and PGI 3 , 6-keto-PGF 1α and d17-6-keto-PGF 1α respectively) clearly indicates the importance of these metabolites despite AA by far has the lowest concentration in cellular membranes compared to EPA and DHA. This further suggests the possible role of phosphatidylinositol phospholipids, being enriched in AA as an important contributor of AA for eicosanoid production, although definitive data are still not available (Tocher 2003). It is also likely that other mechanisms in the eicosanoid signaling pathway have evolved discriminating in favor of AA.…”
Section: Discussionmentioning
confidence: 99%
“…The clear preference of production of PGE 2 over PGE 3 , and a general preference of n-6 eicosanoids over their n-3 counterparts (eg PGF 2α and PGF 3α , and also the stable nonenzymatic hydrolytic products of PGI 2 and PGI 3 , 6-keto-PGF 1α and d17-6-keto-PGF 1α respectively) clearly indicates the importance of these metabolites despite AA by far has the lowest concentration in cellular membranes compared to EPA and DHA. This further suggests the possible role of phosphatidylinositol phospholipids, being enriched in AA as an important contributor of AA for eicosanoid production, although definitive data are still not available (Tocher 2003). It is also likely that other mechanisms in the eicosanoid signaling pathway have evolved discriminating in favor of AA.…”
Section: Discussionmentioning
confidence: 99%
“…In eggs of crucian carp, lipid content ranged from 1.0% to 3.8% (median: 2.9%), which were one order of magnitude lower than those (median: 33%) in northern snakehead (Table 1). It was reported that, for fish with low lipid content eggs (<5%), there were large differences in lipid composition between the eggs and the body (Tocher, 2003). Compared to the mother tissues, these eggs contained a much larger percentage of polar lipids, e.g., phosphatidylcholine (Tocher, 2003); which may affect the partitioning of lipophilic chemicals between the mother and the eggs.…”
Section: Mother-to-egg Transfermentioning
confidence: 99%
“…Therefore, HUFA are essential fatty acids (EFA) for marine fish, and are important as structural components of cell membranes Marsh, 2008), eicosanoids precursors (Tocher, 2003;Bell et al, 2006;Villalta et al, 2007) and regulators of gene expression (Zheng et al, 2005;Miller et al, 2008;Leaver et al, 2008). The fatty acid profile of VO, together with this poor ability of marine fish to convert C 18 polyunsaturated fatty acids (PUFA) to HUFA, lead to important changes in the fatty acid composition of flesh of fish fed VOs, which include decreased n-3 HUFA and increased fat and LA contents Menoyo et al, 2004;Bell et al, 2006;Benedito-Palos et al, 2007;Díaz-López et al, 2009;Fountoulaki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Echium oil (EO) has a good n-3/n-6 PUFA balance as well as an interesting profile with its high content of unusual fatty acids (SDA and GLA) that are of increasing pharmacological interest based on their competitive and inhibitory effects in the production of proinflammatory eicosanoids derived from ARA (Tocher, 2003;Villalta et al, 2007;Chilton et al, 2008;Whelan, 2009). The high levels of SDA, compared to LNA, may also facilitate its conversion into n-3 HUFA, since it does not require the first, rate-limiting, Δ6 desaturation step.…”
Section: Introductionmentioning
confidence: 99%